Effectiveness of Educational Facilities and Infrastructure in Strategic Management Perspective (Case Study at SMA Negeri 2 Dusun Hilir) - Fatrahul Ani; Ahmad Suriansyah; Ratna Purwanti (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
Administration of educational facilities and infrastructure plays an important role in supporting the smooth running of the learning process in schools. This study aims to describe the stages of management of facilities and infrastructure and the role of school residents in its implementation, with a case study at SMA Negeri 2 Dusun Hilir. The method used is qualitative descriptive with interview techniques. The results of the study indicate that management is carried out systematically through six stages: planning, procurement, inventory, maintenance and supervision, deletion, and evaluation and reporting, involving the principal, teachers, and staff. Orderly and participatory management has been shown to increase the effectiveness of learning and the quality of education in schools. Key Words: Effectiveness, Facilities and Infrastructure, School Management Abstrak: Administrasi sarana dan prasarana pendidikan berperan penting dalam mendukung kelancaran proses pembelajaran di sekolah. Penelitian ini bertujuan mendeskripsikan tahapan pengelolaan sarana dan prasarana serta peran warga sekolah dalam pelaksanaannya, dengan studi kasus di SMA Negeri 2 Dusun Hilir. Metode yang digunakan adalah kualitatif deskriptif dengan teknik wawancara. Hasil penelitian menunjukkan bahwa pengelolaan dilakukan secara sistematis melalui enam tahapan: perencanaan, pengadaan, inventarisasi, pemeliharaan dan pengawasan, penghapusan, serta evaluasi dan pelaporan, dengan melibatkan kepala sekolah, guru, dan staf. Pengelolaan yang tertib dan partisipatif terbukti meningkatkan efektivitas pembelajaran dan mutu pendidikan di sekolah. Kata Kunci: : Efektifitas, Sarana dan Prasarana, Manajemen Sekolah